Analisis Perbandingan Hukum Pidana Indonesia dan Malaysia dalam Menangani Kasus Tindak Pidana Korupsi - Dewi, Anies Prima; Iman, Yakin Nur (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Corruption significantly threatens a nation's integrity and impedes development. Both Indonesia (through Law No. 31/1999, amended by Law No. 20/2001) and Malaysia (under the Malaysian Anti-Corruption Commission Act 2009) are working to combat this issue within their respective criminal law frameworks. A comparative analysis of these two systems is essential for understanding their approaches to addressing and resolving corruption cases. Objective: This comparative study aims to identify the fundamental similarities and differences between Indonesia's and Malaysia's criminal law systems concerning corruption. Additionally, it seeks to analyse the advantages and disadvantages of each system in their efforts to combat corruption, ultimately providing comprehensive insights. Method: This study employs a comparative juridical-normative literature review, examining relevant laws and regulations from both countries. Results: Both nations exhibit significant similarities, particularly in establishing special institutions investigating corruption. Indonesia's Corruption Eradication Commission (KPK) and Malaysia's Suruhanjaya Pencegah Rasuah Malaysia (SPRM) exemplify a strong commitment to tackling corruption. However, differences can be observed in their scope of authority, prosecution mechanisms, and sanctions. The KPK in Indonesia benefits from a high level of independence, while Malaysia may have the advantage of more expedited processes. Implementation challenges, including political resistance and resource constraints, may be disadvantages for both systems. Conclusion and Recommendations: The criminal justice systems in Indonesia and Malaysia share a key similarity in forming specialized institutions (the KPK and SPRM) to address corruption. Nevertheless, variations in authority and procedural details impact their overall effectiveness. Further in-depth research is recommended to evaluate the practical implementation, effectiveness of sanctions, and political challenges faced by the KPK and SPRM. Also, fostering an exchange of best practices between the two countries could promote continuous improvement in their efforts against corruption.